Computational study of antimalarial alkaloids of plant origin - Bilonda, Kabuyi Mireille (My University, 2019)
This thesis is concerned with the computational study of naphthylisoquinoline alkaloids having antimalarial properties. The study was considered interesting because of the importance of gathering information on antimalarial molecules and because these molecules had not yet been studied computationally. The alkaloids considered in this study had been isolated from tropical lianas belonging to the Dioncophyllaceae and Ancistrodaceae families. They comprise alkaloids with both monomeric and dimeric structures. The monomeric structures consist of one unit and the dimeric ones of two units, with each unit containing a naphthalene moiety and an isoquinoline moiety. 33 monomeric molecules were studied, which represent a large portion of all the monomeric naphthylisoquinoline alkaloids isolated so far. Two dimeric molecules with antimalarial activity were investigated, namely, jozimine A2 and mbandakamine A. A third dimeric molecule, with a structure close to that of jozimine A2 but different activity (michellamine A, anti-HIV) was also calculated for comparison purposes. This work utilised electronic structures methods and involved the conformational study of all the molecules selected to identify the stabilising factors in vacuo and in solution. Two levels of theory (HF/ 6-31G (d,p) and DFT/B3LYP/ 6-31+G(d,p)) were utilised to compare their performance for compounds of this type, also in view of a future study extending to other compounds of the same class. The molecules were firstly studied in vacuo and secondly in three different solvents – chloroform, acetonitrile and water – characterized by different polarities and different H-bonding abilities. Quantum chemical calculations in solution were carried out using the Polarisable Continuum Model (PCM). The main stabilizing factors are the presence and types of intramolecular hydrogen bonds (IHBs), which are the dominant factors, and also the mutual orientation of the moieties. The possible IHBs comprise OH⋯O (or OH⋯N and NH⋯O for mbandakamine A) and other H-bond types interactions such as OH⋯ and CH⋯O (or CH⋯O and CH⋯N for mbandakamine A). The moieties prefer to be perpendicular one to another, which is a common tendency of aromatic vii systems. In monomeric structures, there may be only one OH⋯O and possibly also one of each of the other two types of IHBs interactions. In dimeric structures, there may be up to four (five in mbandakamine A) OH⋯O IHBs simultaneously and also other H-bond type interactions. The results provide a comprehensive picture of the molecular properties of these compounds, such as conformational preferences, dipole moments, HOMO-LUMO energy gaps, harmonic vibrational frequencies, solvent effect and influence of the solvent on molecular properties which respond to polarisation by the solvent. Altogether, these results may contribute to a better understanding of their biological activity and to the design of molecular structures with enhanced biological activity. This is the reason of focusing the efforts on the investigation of chemical and physical properties of these alkaloids molecules.
Department of Chemistry
PhD (Chemistry)
Keywords: Alkaloids; UCTD; Antimalarials; Computable molecular properties; Intra molecular hydrogen bonding; Naphthylisoquinoline alkaloids; Mutual orientation of aromatic moieties; Solute-solvent interactions; 581.634096; Alkaloids -- Africa; Belladonna (Drug) -- Africa; Plant metabolites -- Africa; Malaria -- Africa; Antimalarials -- Africa